The influence of dietary lysine on carcass characteristics and subprimal cut distribution of high-lean growth gilts fed to 230 and 300 lb - Stuewe, S.R.; Friesen, K.G.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy-two high-lean growth gilts were used to determine the effects of dietary lysine on carcass characteristics and subprimal cut distribution of gilts fed to 230 or 300 lb. The gilts were fed one of six lysine treatments (digestible lysine of .44, .54, .64, .74, .84, and .94% corresponding to .55, .67, .79, .91, 1.03, and 1.15% total lysine, respectively). For gilts fed to 230 or 300 lb, effects on carcass characteristics or subprimal cut distribution were minimal. For gilts fed to 230 lb, only slight linear decreases in 402 ham and boneless 402C ham were observed as dietary lysine increased. Therefore, producers can utilize a level of lysine to maximize growth performance, without negatively affecting carcass characteristics or subprimal cut yields.
Keywords: Swine; Pork; Lysine; Gilts; Meat yield